Study on Effect of Plastic Waste on Softer Grade (Vg-10) Bitumen (International Journal of Innovative Research in Engineering & Management, 2023)
Plastics are useful product but their  disposal as a waste had become a serious problem,  especially in India. Recycling of plastic waste into useful  products is one of the solution for its disposal. Plastic can  be used in the bituminous (asphaltic) pavement  construction which may help in reducing the permanent  deformation in the form of rutting the Pavement surface  and also, its use in bituminous binders helps in the  protection of our environment. PET (Polyethylene  Terephthalate) is a form of plastic waste which is now  being used as packaging material for a wide range of products and also in the packing of carbonated beverages.  In this study, the effects of PET on various properties of  the bitumen are discussed in details. PET was added @  2.5% increment to the bitumen from 0% to 15% and  various tests such as ductility test, penetration test,  specific gravity test, softening point, flash and fire point  and thin film oven test (TFOT) were performed. From the  results of our study, it was inferred that the modified  bitumen inherits better performance when compared to  the virgin bitumen. The most effective percentage of  Polyethylene Terephthalate (PET) waste in our study was  seen between 10 to 12.5% by weight of the bitumen,  beyond 12.5%properties like ductility of bitumen gets reduced. Hence, PET could be used more effectively up to the percentage of 12.5%.
Keywords: Plastic waste (PET); Penetration; Viscosity; Bitumen; TFOT